PEER: PHYSIO-FEEDBACK AND EXERCISE PROGRAM LED BY A TRAINED PEER COACH FOR DIVERSE OLDER ADULTS. (16th November 2018) - Thiamwong, L; Stout, J; Yan, X
Abstract: Promising new physio-feedback technology, which is portable, cost-effective, and easy to use may provide rapid feedback to older adults on their physical abilities and possibly encourage them to participate in an exercise program. The purpose of this study was to examine the efficacy of a Physio-fEedback and Exercise pRogram (PEER) that led by a trained older adult peer coach for ethnically diverse community-dwelling older adults. PEER is a fall prevention program that included physio-feedback technology, the BTrackS Balance System, that allows instant playback showing older adults' static balance capacity and alter perception of fall risk appraisal. In addition, PEER combined the advantages of group-based exercise program with tailored home-based exercise and support from a peer coach. The research design was a quasi-experimental intervention trail with a control group performed at two sites. The 8-week intervention group (n=19) met weekly for 60 minutes and included pre-test, physio-feedback and post-test. This intervention group also completed a 30-minute, home-based exercise at least two days a week. The control group (n=22) was asked to continue their normal activities. Results indicated that the PEER program significantly improved postural sway measured by BTrackS balance test. The intervention group had slightly reduced BTrackS balance score (29.79 ± 15.74 to 26.84 ± 12.21) while the control group had a significant increase in BTrackS balance score (31.77 ± 11.42 to 39.68 ± 10.34). There was no gender and ethnicity effect to the PEER intervention.